Q Factor Based Performance Evaluation of Bidirectional TDM PON Network Using Hybrid Amplifier Configurations - Sharma, D; Payal; Kumar, S (International Journal of Computer Sciences and Engineering, 2025)
Passive Optical Networks (PONs), designed by Full Service Access Network (FSAN) working group, is the converged infrastructure standardized by ITU and IEEE. PONs support services such as traditional telephony, VoIP and various other multimedia services upto a logical reach of 60km with a split ratio of 1:128. Hence to enhance the reach and performance of PONs, one of the foremost solutions is the use of hybrid optical amplifiers. In this present paper, a model of bidirectional Time Division Multiplexing (TDM) PON using hybrid optical amplifiers configuration (Semiconductor Optical Amplifier (SOA), Raman Amplifier and Erbium Doped Fiber Amplifier (EDFA)) is presented. The performance of the designed system is evaluated for variation of Q Factor with transmission distance using (i) SOA-Raman (ii) SOA-EDFA and (iii) EDFA-EDFA hybrid configuration by carrying out simulations.